Implementation of the Regulation of the Mayor of Medan Number 35 of 2020 Regarding the Coordination of the Organization of Public Facilities and Infrastructure Maintenance and Environmental Cleanliness in the District of Medan Sunggal - Putra Ramadhan; Nina Siti Salmaniah Siregar; Syafruddin Ritonga (MultiTech Publisher, 2024)
This research aims to analyze the implementation of the Regulation of the Mayor of Medan Number 35 of 2020 in the Medan Sunggal District related to the coordination of the organization of public facilities and infrastructure maintenance, as well as environmental cleanliness. This regulation was issued to improve the efficiency and effectiveness of public facility maintenance efforts, as well as to encourage community participation in maintaining environmental cleanliness. This research uses a qualitative approach with in-depth interviews with relevant parties, including government agencies, the community, and local figures. The collected data is analyzed using content analysis techniques to identify patterns of regulation implementation and responses from various stakeholders. The results show that the implementation of the Regulation of the Mayor of Medan Number 35 of 2020 in the Medan Sunggal District is not yet fully optimal. Coordination between government agencies still faces obstacles, and community participation in maintaining environmental cleanliness still needs improvement. Ambiguities in task distribution and responsibilities also hinder the implementation of this regulation. This research provides recommendations for local governments to enhance coordination between agencies, provide better understanding to the public about this regulation, and develop clear mechanisms for task distribution and responsibilities. It is hoped that the implementation of this regulation can become more effective and have a positive impact on the maintenance of public facilities and infrastructure, as well as environmental cleanliness in the Medan Sunggal District.